2019
DOI: 10.3390/nu11030578
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols Targeting Arterial Stiffness: Interplay of Contributing Mechanisms and Gut Microbiome-Related Metabolism

Abstract: Increased arterial stiffness is a degenerative vascular process, progressing with age that leads to a reduced capability of arteries to expand and contract in response to pressure changes. This progressive degeneration mainly affects the extracellular matrix of elastic arteries and causes loss of vascular elasticity. Recent studies point to significant interference of dietary polyphenols with mechanisms involved in the pathophysiology and progression of arterial stiffness. This review summarizes data from epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 244 publications
(288 reference statements)
0
43
0
Order By: Relevance
“…Curcumin-PEG-PLA nanoparticles, for example, cross the BBB six- Chlorogenic acid-derived catabolites, such as dihydrocaffeic acid, dihydroferulic acid and feruloylglycine, were also shown to be effective neuroprotectors [45]. Polyphenols also affect the gut microbiota composition, thereby modulating the composition of the metabolites [62]. Thus, the effect of polyphenolic compounds on neurodegeneration is mediated by multiple mechanisms, among which the antiglycating and antioxidant activity of the polyphenols may play a significant role in neuroprotection in AD and other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin-PEG-PLA nanoparticles, for example, cross the BBB six- Chlorogenic acid-derived catabolites, such as dihydrocaffeic acid, dihydroferulic acid and feruloylglycine, were also shown to be effective neuroprotectors [45]. Polyphenols also affect the gut microbiota composition, thereby modulating the composition of the metabolites [62]. Thus, the effect of polyphenolic compounds on neurodegeneration is mediated by multiple mechanisms, among which the antiglycating and antioxidant activity of the polyphenols may play a significant role in neuroprotection in AD and other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that some flavonoids administered orally can decrease arterial blood pressure [1,2]. The bioavailability of parent flavonoids is however low [3] and hence the observed effect could be mediated by their metabolites [4,5]. Although there are some data on conjugates of flavonoids [6], colonic metabolites seem to be more active vasodilators, as was shown recently ex vivo as well as in vivo in spontaneously hypertensive rats (SHR) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are a kind of natural polyphenols, mainly including flavonoids, flavanols, flavonoids, anthocyanins, and isoflavones [225]. Studies had shown that flavonoids had definite efficacy in the treatment of agerelated neurodegenerative diseases [226], cardiovascular diseases [227,228], atherosclerosis [229], etc. Some progress has Modulation of the mitochondrial pathway of apoptosis and the cholinergic system [186] 12…”
Section: Flavonoidsmentioning
confidence: 99%